Jersey : Financial Sector Assessment Program Update; Detailed Assessment of Observance of the Insurance Core Principles. (IMF Staff Country Reports; Country Report ;, 2009)
This report presents a Detailed Assessment of the Observance of the Insurance Core Principles Report on Jersey. Other than the international business, most cover is obtained from insurers based overseas by the large insurance broker community on the island. There is no ombudsman and no policyholder compensation arrangements for insurance business on the island. Jersey has its own company's legislation, but has no local accounting or actuarial standard-setting bodies and it looks to other jurisdictions, especially the United Kingdom, for its framework of accounting, auditing, and actuarial standards.